ANALYSIS OF SALES DECISION ON RICE FARMERS IN BANGSALSARI JEMBER DISTRICT - Suherman, Suherman; Sauqi, Ahmad (AGRIBEST, 2020)
Agriculture can be divided into two, namely in the narrow sense or popular agriculture and in a broad sense. Agriculture in the strict sense includes: agriculture of food crops, vegetables, fruits, and other plants that have the potential to be traded. Some of the difficulties faced by rice farmers at harvest time include: dealing with erratic weather such as the rainy season, lack of infrastructure such as drying floors. Therefore, farmers cannot process their rice production during post-harvest, so that when they want to harvest, farmers are faced with two alternative sales, namely: they want to harvest themselves, then sell them to traders or slash them. The alternative is important in the analysis because it involves the decision of farmers to sell their rice products. The purpose of this study is to determine whether there are differences in yields received by farmers between the two alternative rice sales decisions mentioned above. The determination of the research area was carried out deliberately in Bangsalsari District. Samples were taken with the Snowball technique (Snowball Sampling), the samples taken were 30 rice farmers. The study was conducted in the first planting season (December 2018-March 2019) and the second planting season (April-July 2019). The analytical model used to determine the differences between the two farmers selling decisions is the Mann-Whitney test. The results of the analysis show that the mean rank in self-harvest is 21.17 and the sale of slash is 9.83. The conclusion is that there is a real difference in the results received by farmers between the harvest itself and the sale by slash